2016
DOI: 10.1177/1533034616655658
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pancreatic Cancer Cell Thermal Response to Heat Ablation or Cryoablation

Abstract: One of the most lethal carcinomas is pancreatic cancer. As standard treatment using chemotherapy and radiation has shown limited success, thermal regimens (cryotherapy or heat ablation) are emerging as viable alternatives. Although promising, our understanding of pancreatic cancer response to thermal ablation remains limited. In this study, we investigated the thermal responses of 2 pancreatic cancer cell lines in an effort to identify the minimum lethal temperature needed for complete cell death to provide gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Comparison of heating versus freezing from our previous study [37] indicated that apoptosis was Liver Pancreat Sci, 2017 doi: 10.15761/LPS.1000115 more prominent following freeze exposure and almost completely absent after heating. Even in the case of BxPC-3 samples that possessed an apoptotic peak, once DTA was performed, the levels of apoptosis declined dramatically.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Comparison of heating versus freezing from our previous study [37] indicated that apoptosis was Liver Pancreat Sci, 2017 doi: 10.15761/LPS.1000115 more prominent following freeze exposure and almost completely absent after heating. Even in the case of BxPC-3 samples that possessed an apoptotic peak, once DTA was performed, the levels of apoptosis declined dramatically.…”
Section: Discussionmentioning
confidence: 86%
“…Studies using PaCa cells previously revealed that temperatures below -20 or -25°C were necessary for complete ablation of BxPC-3 and PANC-1 samples, respectively [37]. When PANC-1 cells were exposed to -15°C there was an initial drop in viability; however, samples recovered over the seven-day assessment interval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pro-inflammatory cytokine TNF-a in combination with freezing elevates the lethal temperature to À0.5 C [32]. Similarly, RF ablation [36], radiation with CA [37] and heat plus freezing [38] also enhance tumor cell death. One benefit reported on the use of CA in combination with chemotherapy is the potential to use lower, sub-lethal, doses of chemotherapeutic agents in combination with CA to obtain the desired outcome [4,30,31].…”
Section: Chemotherapeutic Agentsmentioning
confidence: 99%